2021
DOI: 10.1016/j.celrep.2021.109109
|View full text |Cite
|
Sign up to set email alerts
|

Diverse immunoglobulin gene usage and convergent epitope targeting in neutralizing antibody responses to SARS-CoV-2

Abstract: Highlights d 54 antibodies have neutralizing IC 50 values in the range of 3.3-81 ng/mL d Neutralization by 47D1 is achieved without direct blocking of RBD-ACE2 binding d 47D1 binds only to one side of the receptor binding surface on the RBD d Convergent epitope targeting in neutralizing antibody responses to SARS-CoV-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 79 publications
(111 reference statements)
2
28
0
Order By: Relevance
“…Neutralizing antibodies mainly target the RBD and NTD of spike ( 9 , 16 , 17 ). Previous studies have shown that the levels of antibodies against different forms of spike (including S1, S1/S2, and RBD) correlate well with the neutralization capacity of the samples ( 27 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutralizing antibodies mainly target the RBD and NTD of spike ( 9 , 16 , 17 ). Previous studies have shown that the levels of antibodies against different forms of spike (including S1, S1/S2, and RBD) correlate well with the neutralization capacity of the samples ( 27 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over the course of the COVID-19 pandemic, our understanding of the antibody response against SARS-CoV-2 has evolved considerably. Initial investigations suggested that most neutralizing antibodies elicited by infection or vaccination target the RBD ( 9 , 41 ). More recent studies have shown a codominance of antibodies that target the RBD and NTD ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, severe ALI occurred in mice by adapting the virus to mouse ACE2 receptor and inserting the human ACE2 gene. Zhou et al [ 42 ] found that coronavirus entered the host cells by utilizing the spike protein to bind the hydrophobic pocket of the ACE2 extracellular catalytic domain. Once infected by the virus, ACE2 was downregulated in the cell and thus led to a dysregulation of the ACE2/Ang- (1-7)/MasR axis and the ACE/Ang II/AT1R axis [ 43 ].…”
Section: Ace2 and Covid-19mentioning
confidence: 99%
“…The key to vaccine-induced immunity is the ability of the induced antibodies to specifically bind to the SARS-CoV-2 with a strong binding affinity. The complex structures of the antibodies bound to the SARS-CoV-2 S RBD have been experimentally determined by using cryo-electron microscopy (cryo-EM) and X-ray diffraction [12,[16][17][18][19][20][21][22][23][24][25][26][27][28]. In the intracellular environment and in an extracellular medium, protein-protein docking is usually a spontaneous contact of high specificity established between two or more specific protein molecules; erroneous protein-protein docking rarely occurs [29].…”
Section: Introductionmentioning
confidence: 99%